The use of capillary electrophoresis in the simultaneous determination of fixed-dose combination drugs for cardiovascular diseases - Gabriel Hancu (Trends in Pharmaceutical Sciences, 2020)
Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide and are usually multifactorial medical conditions. Usually cardiovascular patients must follow a complicated treatment scheme, containing several drugs. Fixed dose combinations (FDCs) are pharmaceutical formulations containing two or more active ingredients in a one pill. FDCs can add multiple benefits to the treatment of CVDs including increased patient compliance, elimination of some side effects and the simultaneous blockage of multiple pathogenic links. The great prevelance of FDCs in modern therapy brings the necessity of developing new analytical methods for the simultaneous analysis of their components. Capillary electrophoresis (CE) was shown to be as a complementary and attractive alternative to the more frequently used chromatographic methods. CE advantages relate to the high efficiency of separation, rapid method developement, short analysis time and relatively low operational costs. The most frequently used CE techniques in the analysis of FDCs are capilllary zone electrophoresis (CZE) for ionized analytes and micellar electrokinetic chromatography (MEKC) for neutral ones. The current article reviews application of CE in the analysis of FDCs used in the treatment of CVDs.